The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s12011-012-9358-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Serum C-reactive Protein and Serum Zinc, Ferritin, and Copper in Guatemalan School Children

Abstract: Inflammation affects trace nutrient concentrations, but research on copper and particularly in children is limited. We assessed associations between serum C-reactive protein (CRP) and zinc, iron, copper, and other biomarkers (alkaline phosphatase, hemoglobin, and albumin), in 634 healthy 6- to 11-year-old Guatemalan schoolchildren. CRP was measured by a standardized, high-sensitive method. For significant associations with CRP, we stratified nutrient concentrations across categories of CRP and compared concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
(71 reference statements)
3
18
1
Order By: Relevance
“…The finding also indicates that copper-to-zinc ratio correlated positively with CRP. Our finding is consistent with previous study [13]. Some authors reported significant association between inflammation and copper-to-zinc ratio in children while other observed no association [14].…”
Section: Discussionsupporting
confidence: 93%
“…The finding also indicates that copper-to-zinc ratio correlated positively with CRP. Our finding is consistent with previous study [13]. Some authors reported significant association between inflammation and copper-to-zinc ratio in children while other observed no association [14].…”
Section: Discussionsupporting
confidence: 93%
“…In our survey CRP serves mainly as a biomarker of inflammation or subclinical infection on days of blood sampling. A cutoff of >10 mg/L was used for abnormal serum CRP concentrations [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Development of field‐friendly sampling methods has facilitated inclusion of biomarkers in large‐scale international programs such as the Demographic and Health Surveys (D. A. Garrett, Sangha, Kothari, & Boyle, ; McDade et al., ). Biomarkers have been incorporated extensively by anthropologists for population research in non‐Western settings (Gurven et al., ; Leonard et al., ; Worthman & Panter‐Brick, ), including in large birth cohort studies (Bui et al., ; Gettler, McDade, & Kuzawa, ; Kuzawa, Gettler, Muller, McDade, & Feranil, ; McDade et al., ). Nevertheless, our present understanding of human development—both biological and psychobehavioral—is recognized as limited by reliance on a narrow sampling from the wide sociocultural diversity that humans inhabit.…”
Section: Puberty In Global Contextmentioning
confidence: 99%